Design and Development of Electric Motor Controller Trainer: An Instructional Device - Manuel A. Bajet, Jr; Rogelio C. Hidalgo; Nelson A. Bajet (Philippine Association of Institutions for Research, Inc., 2015)
Quality education largely depends on the availability of instructional gadgets and equipment which form collectively as facilities in any learning institutions. Allocated budget in higher education is not sufficient in providing all instructional equipment like in technological courses. This triggered the researchers in developing improvised electric motor controller trainer as an instructional device similar to the commercial ones which will be utilized to reinforce laboratory shop setting. The study used project and developmental method of research; planning, designing and product development testing and revisions were implemented. The descriptive- evaluative research was employed in evaluating the level of acceptability. The newly-developed electric motor controller trainer can do the different activities as compared to the commercial ones: a) Start-Stop-Push button control; b) Start-Stop full- voltage starter with alarm silencing; c) Multiple push button stations; d) Jog motor control; e) Forward reverse motor control (electrical interlocking); f) Automatic forward and reverse motion with limit switches; g) wye-delta reduced voltage starter; and h) Two stages sequential control. The level of acceptability of the trainer is generally assessed by the respondents as very much acceptable in terms of usefulness, effectiveness, functionality, reliability, and safety. Packaging and affordability of the device should be endorsed to the Department of Education for the K-12 curriculum purposes.